A review of thrombotic microangiopathies in multiple myeloma. (October 2019) - Portuguese, Andrew Jay; Gleber, Conrad; Passero, Frank C.; Lipe, Brea
Highlights: Patients with multiple myeloma are uniquely susceptible to developing TMAs. TMA triggers include proteasome inhibition, BMT, and progression of myeloma. Complement-mediated TMAs require prompt terminal complement inhibition. Abstract: Patients with multiple myeloma (MM) are susceptible to developing thrombotic microangiopathies (TMAs), an etiologically diverse group of syndromes which include atypical hemolytic uremic syndrome (aHUS) and thrombotic thrombocytopenic purpura (TTP). The TMAs are characterized by thrombocytopenia and microangiopathic hemolytic anemia (MAHA), and are associated with a high mortality risk and irreversible end-organ damage when treatment is delayed. In MM patients, TMAs may be triggered by specific chemotherapies, bone marrow transplantation (BMT), and progression of underlying disease. Because many characteristics of TMAs overlap with sequelae of MM and its treatments, diagnosis requires a high index of suspicion. Furthermore, our understanding of optimal treatments for these entities is rapidly evolving and clinical practice guidelines do not yet exist. Historically, consideration of a diagnosis of TMA has prompted initiation of therapeutic plasma exchange. In this review, we present an overview of the MM-related TMAs, an approach to workup and diagnosis, and argue for initial empiric MM-related TMA treatment with eculizumab rather than plasma exchange.